2001
DOI: 10.1006/dbio.2001.0153
|View full text |Cite
|
Sign up to set email alerts
|

CPEB Degradation during Xenopus Oocyte Maturation Requires a PEST Domain and the 26S Proteasome

Abstract: Cytoplasmic poly(A) elongation is widely utilized during the early development of many organisms as a mechanism for translational activation. Targeting of mRNAs for this mechanism requires the presence of a U-rich element, the cytoplasmic polyadenylation element (CPE), and its binding protein, CPEB. Blocking cytoplasmic polyadenylation by interfering with the CPE or CPEB prevents the translational activation of mRNAs that are crucial for oocyte maturation. The CPE sequence and CPEB are also important for trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 57 publications
2
68
0
Order By: Relevance
“…Another interesting feature of the SIRT1 protein is the presence of the PEST sequence at residues 525-550 and 667-697. The PEST sequence acts as a signal peptide for protein degradation, and this cleavage is possibly mediated via the proteasome or calpain (56,57). The presence of two PEST regions in SIRT1 is correlated with rapid degradation of the protein by 26 S proteasome protease.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting feature of the SIRT1 protein is the presence of the PEST sequence at residues 525-550 and 667-697. The PEST sequence acts as a signal peptide for protein degradation, and this cleavage is possibly mediated via the proteasome or calpain (56,57). The presence of two PEST regions in SIRT1 is correlated with rapid degradation of the protein by 26 S proteasome protease.…”
Section: Discussionmentioning
confidence: 99%
“…Because the molecular structure of CPEB has been thoroughly examined (26,27), further structure/ function analysis with previously characterized deletion mutants of CPEB allowed us to identify which CPEB functions are most critical for different aspects of neuronal development and circuit function. Using time-lapse imaging, we found that expressing delCPEB, which interferes with CPEB's activity-dependent mRNA polyadenylation but leaves dendritic mRNA transport intact, impairs dendritic-arbor development and the integration of neurons into the visual circuit.…”
Section: Discussionmentioning
confidence: 99%
“…The second deletion mutant (delCPEB; ⌬124-258) lacks the phosphorylation site targeted by aurora kinase and ␣CaMKII. Because it is not activated by phosphorylation (26,27), delCPEB can stably bind and transport mRNA (28) but interferes with the activity-dependent polyadenylation and translation initiation of CPEB mRNA targets. We verified in the retinotectal system that expression of delCPEB interferes with CPEB-dependent protein synthesis in a blind study that compared tissue plasminogen activator (tPA) immunofluorescence in tectal cells expressing del-CPEB, CPEB1, or YFP alone with untransfected neighboring neurons (Fig.…”
mentioning
confidence: 99%
“…We previously identified a possible PEST (proline-, glutamate-, aspartate-, serine-, and threonine-rich) se- quence between 171 and 196 [17]. PEST sequences have been shown to be proteolysis signals in many proteins [29][30][31]. To test whether this PEST motif targets the KLF5 protein for degradation, we generated two KLF5 C-terminus truncated mutants KLF5(1-237) and KLF5(1-171)-His.…”
Section: 2mentioning
confidence: 99%